Post-Colonial Approaches to Translation Studies: An Overview - Ilyas, Farzana; Shahid, Dr. Shahid Hussain (University of Wah Journal of Social Sciences, 2020)
In this new age, translation studies draw more interest as the trend grows. Postcolonial Theory identifies a body of thinking that is generally concerned with the political, aesthetic, technological, historical and social impact of European colonial rule across the world from the 18th to the 20th century. This study aims to spot the postcolonialism focusing on a variety of its translation approaches. It traces two parallel lines of the puzzle over translation. One of which focuses on unequal power relations between cultures, and the second one distinguishes post-colonial translation approaches by analyzing intercultural interactions in environments characterized by uneven power relations. The two lines mainly contributed to illuminate the role of power in the production and reception of translations. However, it is not clear that the post-colonial paradigm can be extended to multiple interlingual interactions with a marginal difference of power relations. Postcolonial approaches are mainly concerned with cultural translation, power, and hybridity, which are figuratively interpreted as a transition between cultures, and have had little respect for language concerns. Whereas, translation studies emphasize on the standard of translation as a linguistic observe that requires intercultural mediation.